The relationships among attitude towards sports, loneliness and happiness in adolescents - Yavuz, Cumaali (Horizon Research Publishing, 2019)
The aim of the study is to investigate the relationship between the attitude towards sports, loneliness and happiness in adolescents. The study was conducted with a total of 403 high school students including 197 females and 206 males. For the data collection, the Oxford Happiness Questionnaire Short Form (OHQ-SF), the UCLA Loneliness Scale (ULS), the Attitude towards Sports Scale (ATSS) and personal information form were used. The analyses were conducted with the structural equation modeling (SEM). According to the findings of the study, a negative correlation was found between adolescents’ attitudes towards sports and loneliness. The relationship between loneliness and happiness was also observed to be negative. As a result of the research, it was observed that adolescents' attitudes towards sports and loneliness were negatively related. In addition, loneliness was negatively correlated with happiness. © 2019 by authors, all rights reserved.
Keywords: Adolescents; Happiness; Loneliness; Sports